Элементный состав Aristolochia clematitis L. - Остапко, И.Н.; Купенко, Н.П. (Донецький ботанічний сад НАН України, 2007)
Изучен элементный состав Aristolochia clematitis L., выращенной в Донецком ботаническом саду НАН
Украины. По Fe, Cd, Zn, Pb отмечено некоторое превышение санитарно-гигиенических норм. Подчёркнуто,
что сбор растительного сырья в качестве источника микроэлементов рекомендуется проводить вдали от
промышленных предприятий. Element composition of Aristolochia clematitis L. which was raised in the Donetsk Botanical Gardens, Nat. Acad.
Sci. of Ukraine is examined. Some exedeengs of maximum permissible concentration of Fe, Cd, Zn, Pb are revealed.
Therefore, gathering of row material of the investigated species as source of microelements is recommended to be
carried out far from industrial enterprises.